2019
DOI: 10.1186/s13045-019-0828-0
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of breast cancer and attributable risk factors in 195 countries and territories, from 1990 to 2017: results from the Global Burden of Disease Study 2017

Abstract: Background: Statistical data on the incidence, mortality, and burden of breast cancer and the relevant risk factors are valuable for policy-making. We aimed to estimate breast cancer incidence, deaths, and disability-adjusted life years (DALYs) by country, gender, age group, and social-demographic status between 1990 and 2017. Methods: We extracted breast cancer data from the 2017 Global Burden of Disease (GBD) study from 1990 through 2017 in 195 countries and territories. Data about the number of breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
234
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 277 publications
(261 citation statements)
references
References 30 publications
(28 reference statements)
5
234
1
1
Order By: Relevance
“…The standardized methods of the Global Burden of Disease Study 2017 have been reported [ 15 ]. To eliminate the effect of age composition from comparisons across various geographical regions or time periods, we used the ASIR, ASDR, and age-standardized DALY rate (per 100,000 populations) [ 20 ]. We generated the 95% uncertainty intervals (UI) for all reported data.…”
Section: Methodsmentioning
confidence: 99%
“…The standardized methods of the Global Burden of Disease Study 2017 have been reported [ 15 ]. To eliminate the effect of age composition from comparisons across various geographical regions or time periods, we used the ASIR, ASDR, and age-standardized DALY rate (per 100,000 populations) [ 20 ]. We generated the 95% uncertainty intervals (UI) for all reported data.…”
Section: Methodsmentioning
confidence: 99%
“…Despite current chemotherapeutic regimens that evidently improved the survival of metastatic tumors, nearly all HER-2+ BC patients nally develop into resistance [25,26].LncRNAs are dysregulated invarious cancers, and modulates drug resistance byinteracting with RNA and proteins [27]. Until now, the precise regulatory mechanisms by which lncRNAs regulate trastuzumab resistance in BC is still not clearlyde ned.…”
Section: Discussionmentioning
confidence: 99%
“…Genetics and genomics have contributed to revolutionizing the diagnostic approach as well as the prognosis and outcomes of breast tumor, paving the way for personalized and tailored ad hoc treatments, which are currently under experimentation [2]. Breast tumor is still, however, a leading cause of mortality [1], with an increased incidence up to 1,960,681 cases, contributing to 17,708,600 disability-adjusted life years (DALYs) in 2017 [3].…”
Section: Breast Cancermentioning
confidence: 99%